Comprehensive analysis of untargeted metabolomics and lipidomics in girls with central precocious puberty - Zhao, Hong-Ying; Zhang, Ya-Rong; Zhang, Ran; Li, Yu-Ting; Guo, Rong-Lian; Shi, Wen-Sheng (Frontiers in Pediatrics, 2023)
Objective: Central precocious puberty (CPP) is a rare condition that causes early sexual development in children. Although the cure is effective, the etiology of central precocious puberty is unclear. Methods: In total, 10 girls with central precocious puberty and same number of age-matched female controls were enrolled. Plasma samples were collected from each participant and subjected to untargeted metabolomics and lipidomics. Student’s t-tests were employed to compare the mean of each metabolite and lipid. Furthermore, orthogonal partial least-squares discriminant analysis was conducted and the variable importance in the projection was calculated to identify differentially expressed metabolites or lipids. Subsequent bioinformatics was conducted to investigate the potential function of differentially expressed metabolites and lipids. Results: Fifty-nine differentially expressed metabolites were identified based on the criteria used (variable importance in the projection >1 and a P value <0.05). Kyoto Encyclopedia Genes and Genome (KEGG) enrichment analysis showed that differentially expressed metabolites were enriched in four pathways: beta-alanine metabolism, histidine metabolism, bile secretion, and steroid hormone biosynthesis. As for the lipidomics, 41 differentially expressed lipids were observed and chain length analysis and lipid saturation analysis yielded similar results. Significant differences between the two groups were only observed in (O-acyl) ω-hydroxy fatty acids (OAHFA). Conclusion: The present study showed that antibiotic overuse, increased meat consumption, and obesity may have potential roles in the development of central precocious puberty in girls. Several metabolites have diagnostic value but further research is required.